Comparing high and low performers for noise control. Issue 1 (9th March 2015) - Bell, Nikki; Lunt, Jennifer; Webster, Jennifer; Ward, Tim
Abstract : Purpose: – The purpose of this paper is to investigate the dimensions that distinguish high from low performing manufacturing companies in Great Britain with respect to controlling noise. The findings should assist regulators and industry to develop interventions that help organisations to effectively manage noise, particularly amongst the low performers. Design/methodology/approach: – The research uses quantitative and qualitative methods. Survey data was obtained from 215 manufacturers and supplemented with 15 qualitative interviews to assess performance and individual, social, environmental and organisational influences on duty holders' decision making for controlling noise. Findings: – Relative to low performers, decision makers from high performing companies had: greater in-depth knowledge of noise risks and controls; taken steps to promote positive health and safety attitudes and values; were large companies; and faced fewer resource barriers (time, costs, staffing). Managers in small, low performing companies sought simple interventions with a practical focus. Research limitations/implications: – The differences reported between high and low performing companies showed a small magnitude of effect but these are considered significant in a health and safety context. Practical implications: – Improvements in training and education, and addressing workplace health and safety culture, are recommended as offering most potential to raise the standard of noise control. Originality/value: – To the authors' knowledge, this is the first study to systematically assess the specific knowledge, attitudes, values and beliefs that employers hold about noise and the influence of social, environmental and organisational factors on manager's decisions about noise controls.